THE EFFECT OF MORINGA LEAF DECOCTION ON BLOOD GLUCOSE REDUCTION AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS - Lenta Dwi Novita Zebua; Amanda Napa Erlita Ritonga; Denvis Notatema Zai; Krisnatalia Br Rajagukguk; Mawazini Adila; Chrismis Novalinda Ginting (Universitas Nahdlatul Ulama Surabaya, 2026)
Background: Type 2 diabetes mellitus remains a major metabolic disorder characterized by chronic hyperglycemia, and long-term pharmacological therapy may cause adverse effects, highlighting the need for safe complementary interventions. Moringa oleifera leaves contain bioactive compounds with potential antihyperglycemic properties. Objective: The aim of this study is to examine the effect of consuming Moringa oleifera leaf decoction on the reduction of blood glucose levels among individuals with type 2 diabetes mellitus. Methods: This study used a quantitative quasi-experimental one-group pretest - posttest design. The independent variable was the administration of Moringa oleifera leaf decoction, while the dependent variable was blood glucose level. Twenty participants with type 2 diabetes mellitus were recruited using accidental sampling. The intervention was given once daily for seven days. Blood glucose levels were measured before and after the intervention, and data were analyzed using the Wilcoxon signed-rank test. Results: Prior to the intervention, most participants had blood glucose levels between 180 - 199 mg/dL, which decreased to 140 - 159 mg/dL after the intervention. Statistical analysis showed a significant difference (p < 0.05). Conclusion: Moringa oleifera leaf decoction may reduce blood glucose levels and could be considered as a complementary intervention for patients with type 2 diabetes mellitus.